Glutamate transporters: confining runaway excitation by shaping synaptic transmission - Tzingounis, Anastassios V.; Wadiche, Jacques I. (Nature reviews. Neuroscience, 2007)
Key Points Excitatory amino-acid transporters (EAATs) terminate glutamate's actions and thus maintain proper neuronal function. These proteins are expressed in vast quantities by glia, but are also present in neurons. Glutamate uptake is coupled to the cotransport of three Na + ions and one H + ion, and the countertransport of one K + ion. This stoichiometry is responsible for keeping the tonic extracellular glutamate concentration at ∼25 nM: below that which is required to significantly activate receptors. In addition to the coupled ions, glutamate transporters allow an uncoupled anion flux. This anion conductance is thought to reflect the occupancy of glutamate-bound conformations, and allows the direct measurement of the activity of transporters. The affinity constants measured from peak currents of neuronal transporters predict that they behave as buffers to rapidly bind released glutamate molecules, whereas the affinities of the more numerous glial transporters predict that they act also as sinks, removing glutamate from the extracellular space. At Schaeffer collateral–CA1 synapses in the hippocampus, glial transporters are responsible for taking up more than 80% of the released glutamate, whereas the neuronal transporters limit spillover between synapses. In the cerebellum, like in the hippocampus, glial transporters are responsible for the bulk of glutamate uptake, whereas the neuronal transporter EAAT4, which is found exclusively in Purkinje cells, regulates extrasynaptic receptor activation and subsequent cerebellar plasticity. At retinal synapses, unlike in any other brain region, presynaptic glutamate transporters act as Cl − channels, rather than transporters, to reduce vesicular release at individual boutons. The high concentration of EAATs around synapses ensures that unbound glutamate will encounter available transporters. Together, rapid sequestration, low capture efficiency and the high concentration of EAATs lead to the buffered diffusion of glutamate, which prevents it spilling back into the synapse. It has become apparent that, in addition to removing excess extracellular glutamate, glutamate transporters can help to shape synaptic events. Tzingounis and Wadiche review the structural properties and regulation of glutamate transporters, highlighting their diverse roles in key brain regions. Traditionally, glutamate transporters have been viewed as membrane proteins that harness the electrochemical gradient to slowly transport glutamate from the extracellular space into glial cells. However, recent studies have shown that glutamate transporters on glial and neuronal membranes also rapidly bind released glutamate to shape synaptic transmission. In this Review, we summarize the properties of glutamate transporters that influence synaptic transmission and are subject to regulation and plasticity. We highlight how the diversity of glutamate-transporter function relates to transporter location, density and affinity.